Fetal origins of autism spectrum disorders: the non-associated maternal factors. (June 2016) - Moussa, Hind N; Srikrishnan, Anand; Blackwell, Sean C; Dash, Pramod; Sibai, Baha M
Aim: Several population-based studies have been conducted to determine whether maternal exposures are involved in the pathophysiology of autism spectrum disorder (ASD). We review these studies and describe the factors not associated with increased risk for ASD development.Methods: We identified studies describing associations between maternal exposures and ASD development. These studies include the Childhood Autism Risks from Genetics and the Environment, Nurses' Health Study II, and the Swedish population registry.Results: Factors not associated with ASD development include Type 2 and gestational diabetes, chronic hypertension, fever treated with antipyretic medication, autoimmune disease and short interpregnancy intervals.Conclusion: There is increasing evidence that maternal exposures are involved in the pathophysiology of ASD in the developing fetus. Lay Abstract: Autism spectrum disorder currently affects one in 68 children in the USA, with up to one in 42 boys. Its underlying etiology is largely unknown. Although autism was once considered a childhood disease, efforts for early detection led to the realization that it might originate at a much earlier stage, namely fetal life. Several maternal risk factors have recently been studied to establish associations with autism in the offspring. In this review, we present the maternal risk factors that were not found to have such associations.